Eksplorasi kreatifitas desain melalui konsep upcycle material produk furnitur paska pakai - Tri Noviyanto P Utomo; Yusita Kusumarini; Stephanus Evert Sindrawan (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2021)
The number of post-use or damaged furniture products before their time becomes a problem especially for ecological problems in the work environment. This research tries to explore the creativity of product design based on the principles derived from the concept of green design. One of the principles of green design derived is the upcycle concept. Through the upcycle concept approach, this research tries to construct ex office material into an explorative and ecological new design. This research uses a case study of ex office / campus furniture products that are no longer in use due to damage. The design model based on upcycle concept and formalistic design is used as a basis for design and to analyze design results. The results of this study in addition to creating explorative design products, also explain the principles of ecological regenerative design values, namely optimizing the use of waste materials, durability of product life that can be extended, as well as supporting environmental protection and increasing product values and aesthetics.